Hyperbole in English a corpus-based study of exaggeration - Claridge, Claudia (Cambridge, United Kingdom Cambridge University Press, 2011)
"Non-literal language is ubiquitous in everyday life, and while hyperbole is a major part of this, it has so far remained relatively unexplored. This volume provides the first investigation of hyperbole in English, drawing on data from genres such as spoken conversation, TV, newspapers, and literary works from Chaucer to Monty Python. Combining quantitative and qualitative analyses, it uses approaches from semantics, pragmatics, discourse analysis and classical rhetoric, to investigate in detail both speaker-centered and emotive aspects of hyperbole, and also addressee-related aspects, such as interpretation and interactional uptake. Illustrated with a range of diachronic case studies, hyperbole is also shown to be a main means of linguistic creativity, and an important contributor to language change. The book concludes with an exploration of the role of hyperbole in political speaking, humour, and literature. Original and in-depth, it will be invaluable to all those working on meaning, discourse, and historical linguistics"--Provided by publisher.
Introduction -- The characteristics of hyperbole -- Realisations of hyperbole -- Using hyperbole: the speaker perspective -- Hyperbole in interaction -- Conventionalisation -- The rhetoric of hyperbole -- Conclusion -- Appendix 1: Modern corpora used -- Appendix 2: Modern sources other than corpora -- Appendix 3: Conventionalisation in dictionaries -- Appendix 4: corpora, dictionaries and texts used for the diachronic investigation.
Includes bibliographical references and index.
Keywords: English language -- Idioms; Figures of speech; Exaggeration (Philosophy); Corpora (Linguistics)